2017
DOI: 10.3390/ijms18030593
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Transcriptome Profiles of Mice with Diet-Induced Nonalcoholic Steatohepatitis Treated with Astaxanthin and Vitamin E

Abstract: Astaxanthin alleviates hepatic lipid accumulation and peroxidation, inflammation, and fibrosis in mice with high-cholesterol, high-cholate, and high-fat (CL) diet-induced nonalcoholic steatohepatitis (NASH). It has been proposed as a potential new treatment to inhibit the progression of NASH in humans. In this study, we compared hepatic gene expression profiles after treatment with astaxanthin or the antioxidant vitamin E in mice with CL diet-induced NASH. Comprehensive gene expression analyses of the livers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In terrestrial animals, although varied results have been observed regarding the effects of dietary ASTX on lipid accumulation, most results indicated that ASTX has a lipid‐lowering effects, either on liver or on plasma and adipose tissue (Bhuvaneswari et al, ; Hussein et al, ; Jia et al, ; Kobori et al, ; McCarty, ; Yang et al, ). Studies in mice fed a high‐fat diet showed that oral ASTX (6 and 30 mg/kg body weight; in olive oil) treatment for 8 weeks lowered hepatic lipid accumulation via activation of PPARα and inhibition of PPARγ and Akt‐mTORC1 signalling (Jia et al, ; Kobori et al, ). However, findings of another in vitro study indicated that ASTX functions differently as a selective PPARγ modulator, as an antagonist or agonist depending on the cell context (Inoue et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terrestrial animals, although varied results have been observed regarding the effects of dietary ASTX on lipid accumulation, most results indicated that ASTX has a lipid‐lowering effects, either on liver or on plasma and adipose tissue (Bhuvaneswari et al, ; Hussein et al, ; Jia et al, ; Kobori et al, ; McCarty, ; Yang et al, ). Studies in mice fed a high‐fat diet showed that oral ASTX (6 and 30 mg/kg body weight; in olive oil) treatment for 8 weeks lowered hepatic lipid accumulation via activation of PPARα and inhibition of PPARγ and Akt‐mTORC1 signalling (Jia et al, ; Kobori et al, ). However, findings of another in vitro study indicated that ASTX functions differently as a selective PPARγ modulator, as an antagonist or agonist depending on the cell context (Inoue et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial animals, many studies indicated that ASTX exerts lipid‐lowering effect via enhancing β‐oxidation (Aoi et al, ; Kim et al, ). Besides the activation of PPARα in mice by ASTX, a study with apolipoprotein E knockout mice also showed that when fed a high‐fat diet, mice fed ASTX (0.03% in the diet) for 4 weeks had increased gene expression of enzymes important for β‐oxidation (e.g., CPT1 and acyl‐CoA oxidase (ACOX)) (Yang et al, ), although there was also a study showing ASTX suppressed the actions of PPARα and the gene expression of its related molecules CPT1α and ACOX1 (Kobori et al, ). In the present study, the gene expression of CPT1 in liver was increased by both 50 and 100 mg/kg dietary ASTX, indicating that ASTX may enhance β‐oxidation in fish too.…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin-associated protection against aging as well as cardiovascular and cancerous diseases is attributed to its great antioxidative and anti-inflammatory activity [ 4 ]. In particular, it has been suggested that astaxanthin is protective against various types of liver damage [ 6 , 7 ], such as non-alcoholic fatty liver disease (NAFLD) [ 8 , 9 , 10 ] and liver fibrosis [ 11 ]; however, further investigation is required to determine the effect of astaxanthin on AFLD protection.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E showed some morphological improvements in NASH [142] and effectively improves gene expression associated with eukaryotic initiation factor-2 signaling, which is suppressed in NASH by endoplasmic reticulum stress in the liver [143]. Supplementation of more than 55.5 mg/kg vitamin E may improve growth and increase of n − 3 long chain polyunsaturated fatty acids content in blunt snout bream, while the expressions of PPAR-α, PPAR-β, and PPAR-c in liver were downregulated, which is beneficial to human consumer [144].…”
Section: Vitamin Ementioning
confidence: 99%